Large-Scale Synthesis of Highly Uniform Silicon Nanowire Arrays Using Metal-Assisted Chemical Etching - Wendisch, Fedja J. (Chem Mater, 2020)
[Image: see text] The combination of metal-assisted chemical etching (MACE) with colloidal lithography has emerged as a simple and cost-effective approach to nanostructure silicon. It is especially efficient at synthesizing Si micro- and nanowire arrays using a catalytic metal mesh, which sinks into the silicon substrate during the etching process. The approach provides a precise control over the array geometry, without requiring expensive nanopatterning techniques. Although MACE is a high-throughput solution-based approach, achieving large-scale homogeneity can be challenging because of the instability of the metal catalyst when the experimental parameters are not set appropriately. Such instabilities can lead to metal film fracture, significantly damaging the substrate and thus compromising the nanowire array quality. Here, we report on the critical parameters that influence the stability of the metal catalyst layer for achieving large-scale homogeneous MACE: etchant composition, metal film thickness, adhesion layer thickness, nanowire diameter and pitch, metal film coverage, Si/Au/etchant interface length, and crystalline quality of the colloidal template (grain size and defects). Our results investigate the origin of the catalyst film fracture and reveal that MACE experiments should be optimized for each Si wire array geometry by keeping the etch rate below a certain threshold. We show that the Si/Au/etchant interface length also affects the etch rate and should thus be considered when optimizing the MACE experimental parameters. Finally, our results demonstrate that colloidal templates with small grain sizes (i.e., <100 μm(2)) can yield significant problems during the pattern transfer because of a high density of defects at the grain boundaries that negatively affects the metal film stability. As such, this work provides guidelines for the large-scale synthesis of Si micro- and nanowire arrays via MACE, relevant for both new and experienced researchers working with MACE.